Preludio de una emancipación: la emergencia de la mujer - Capel Martínez, Rosa M.ª (Cuadernos de Historia Moderna, 2008)
The conquest of enfranchisement for women constitutes one of the signs of identity of the feminist movement born in the XIXth century. However, neither feminism nor assertion of the right to the vote were creations “ ad novo ” of the industrialized, bourgeouis, liberal and democratic world. Its roots can be traced back to the XVIIIth century and the Enlightenment. The present article focuses on these first moments and the reasons that led a minority group of men and women to question masculine domination. They spoke, for the first time, about the rights due to this part of the population, included politicians, and articulated a "corpus” of solidly based arguments to defend their convictions.
Keywords: Suffragism; Universal suffrage; Woman; XVIIIth Century; Enlightenment